2008
DOI: 10.1093/carcin/bgn133
|View full text |Cite
|
Sign up to set email alerts
|

Differential cancer predisposition in Lynch syndrome: insights from molecular analysis of brain and urinary tract tumors

Abstract: Hereditary non-polyposis colorectal carcinoma (Lynch syndrome) is among the most common hereditary cancers in man and a model of cancers arising through deficient DNA mismatch repair (MMR). Lynch syndrome patients are predisposed to different cancers in a non-random fashion, the basis of which is poorly understood. We addressed this issue by determining the molecular profiles for different tumors from a nationwide cohort of Lynch syndrome families (approximately 150 tumors in total). We focused on some less pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
94
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 65 publications
6
94
0
Order By: Relevance
“…These abnormalities were also associated with urothelial neoplasms, particularly of the ureter and renal pelvis. 26 Patients at risk have an approximately 22-fold increased relative risk of developing UTUC. 27 The lifetime risk for urological cancer has been estimated to be approximately 8% by age 70 years, 26 and that is why some guidelines and experts recommend that all UTUC patients should be screened for HNPCC spectrum disease though a short interview, and should undergo DNA sequencing if they fulfill all criteria for HNPCC.…”
Section: Genetic Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…These abnormalities were also associated with urothelial neoplasms, particularly of the ureter and renal pelvis. 26 Patients at risk have an approximately 22-fold increased relative risk of developing UTUC. 27 The lifetime risk for urological cancer has been estimated to be approximately 8% by age 70 years, 26 and that is why some guidelines and experts recommend that all UTUC patients should be screened for HNPCC spectrum disease though a short interview, and should undergo DNA sequencing if they fulfill all criteria for HNPCC.…”
Section: Genetic Effectsmentioning
confidence: 99%
“…26 Patients at risk have an approximately 22-fold increased relative risk of developing UTUC. 27 The lifetime risk for urological cancer has been estimated to be approximately 8% by age 70 years, 26 and that is why some guidelines and experts recommend that all UTUC patients should be screened for HNPCC spectrum disease though a short interview, and should undergo DNA sequencing if they fulfill all criteria for HNPCC. 28 If DNA sequencing confirms the diagnosis of HNPCC syndrome, patients should undergo a clinical evaluation for other HNPCC-related cancers, a close follow up and familial genetic counseling.…”
Section: Genetic Effectsmentioning
confidence: 99%
“…Using a national cohort of Lynch syndrome families from Finland, Gylling et al found that brain tumors were diagnosed at the average age of 38 years and that glioma was the most common histologic subtype [11]. Watson et al utilized a cohort of 6,176 members of 261 families to document that the risk of brain cancer in Lynch syndrome showed an overall lifetime risk of 2% [12].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of inactivation of both allelic copies, tumor tissues from LS patients typically show the absence of the respective MMR protein by immunohistochemical analysis (and occasionally, other MMR proteins as well in a defined pattern . This has been shown to apply to almost all colorectal carcinomas and extracolonic cancers of the LS spectrum, and brain tumors are no different (Gylling et al, 2008). Inactivation of a MMR gene is believed to initiate tumorigenesis through the failure of one or several essential functions that the MMR system is known to have, including repair of replication errors and a role in DNA damage signaling (Jiricny, 2006).…”
Section: Tumorigenic Mechanismsmentioning
confidence: 99%